Pengembangan Kurikulum ISMUBA dalam Meningkatkan Kualitas Pendidikan Muhammadiyah - Mundofi, Ahmad Asron (Universitas Muhammadiyah Yogyakarta, 2024)
The development of curricula is a critical aspect in creating quality education that is relevant to religious values. This study deals with the